The role of Xpert MTB/RIF using bronchoalveolar lavage fluid in active screening: insights from a tuberculosis outbreak in a junior school in eastern China - Wu, Qian; Wu, Kun-Yang; Zhang, Yu; Liu, Zheng-Wei; Chen, Song-Hua; Wang, Xiao-Meng; Pan, Jun-Hang; Chen, Bin (Frontiers in Public Health, 2023)
Tuberculosis (TB) outbreaks in schools present a public health challenge. In order to effectively control the spread of transmission, timely screening, accurate diagnosis and comprehensive epidemiological investigations are essential. In July 2021, a TB outbreak occurred in a junior high school in Y City, Zhejiang Province. Students and faculty were screened for TB by symptom screening, chest radiography, and tuberculin skin test during four rounds of contact screenings. For sputum smear-negative and sputum-scarce patients, bronchoscopy was used to collect BAL samples for Xpert Mycobacterium tuberculosis/rifampin (MTB/RIF). Whole-genome sequencing and bioinformatics analysis were performed on isolates to identify the strains of MTB isolates and predict drug resistance. Between July 2021 and November 2021, a total of 1,257 students and faculty were screened for TB during screenings. A total of 15 students (1.2% of persons screened) aged 15 years were diagnosed with TB. Eighty percent (12/15) of the cases were laboratory-confirmed (10/12 [83%] Xpert MTB/RIF-positive, 2/12 [17%] culture-positive). Most cases (12/15 [80%]) were in students from Class 2. All cases were asymptomatic except for the index case who had symptoms for more than two months. Seven MTB isolates were collected and belonged to lineage 2. Our findings demonstrated the potential of Xpert MTB/RIF using BAL as a screening tool in school TB outbreaks for sputum smear-negative and sputum-sparse suspects, which may not only rapidly improves diagnostic accuracy, but also facilitates epidemiological investigations and homology analysis.